Synthesis and physico-mechanical analysis of graphene nanoplatelets (GNPs) filled natural rubber/ethylene propylene diene monomer (NR/EPDM) for vibration resistance - Yaakub, Juliana (2015)
In recent years, polymer nanocomposites have attracted great interest due to their remarkable improvements in materials properties when compared with virgin polymer or conventional micro and macro-composites. This research is an effort to explore the potential of graphene nanoplatelets (GNPs) filled natural rubber/ethylene-propylene-diene rubber (NR/EPDM) as mount rubber based on their physico-mechanical and vibration damping properties. At stage 1, the effects of compatibilizer and processing parameters on the properties of NR/EPDM (70: 30 phr) blends were studied. The blends were prepared by melt compounding using Haake Internal Mixer. Using Response Surface Methodology (RSM) of two-level full factorial, the effects of epoxidized natural rubber, ENR-50 contents (-1:5 phr; +1:10 phr), mixing temperature (-1:50 °C; +1:110 °C), rotor speed (-1:40 rpm; +1: 80 rpm) and mixing time (-1:5 min; +1:9 min) in NR/EPDM blends were evaluated. Cure characteristics and tensile properties were selected as the responses. The coefficient of determination, R2 values above 0.90 were accurate to represent the actual system. The findings were further supported by swelling behaviour, thermal and morphological characteristics. At stage 2, a facile method for surface treatment of GNPs was demonstrated. In stage 3 and 4, the effects of unfunctionalized and functionalized GNPs loading (0, 0.25, 0.50, 1, 3 and 5 wt%) on cure characteristics, physico-mechanical, structural, vibration, thermal properties of the composites as well as on their morphologies were studied. The studies were carried out through Monsanto rheometer analysis, tensile test, swelling test, X-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), vibration test, dynamic mechanical analysis (DMA), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) analysis. The GNPs show good compatibility with NR/EPDM matrix due to their improvement observed in cure characteristics, tensile properties and crosslink density compared with unfilled vulcanized NR/EPDM. It was in line with the observation on structural and chemical properties of GNPs dispersed in NR/EPDM matrix. XRD and FTIR pattern have provided sufficient explanation regarding the state of dispersion of GNPs filled NR/EPDM matrix. The morphology of the unfunctionalized and functionalized GNPs in the NR/EPDM matrix revealed uniform distribution of GNPs up to 3 wt% loading, whereas, GNPs agglomerates were observed at 5 wt%. The vibration test via free vibration test had proven the potential of GNPs filled NR/EPDM as mount rubber in which their amplitude decays faster than the vulcanized NR/EPDM. The storage modulus, loss modulus and tan δ showed good agreement with the vibrational damping behaviours. TEM analysis revealed the existence of intercalated and exfoliated structure of GNPs which resulted in improved vibration damping characteristics and mechanical properties. In overall, GNPs filled NR/EPDM are capable to absorb vibrational energy particularly for a mount rubber.